Implementation of Trusted Third Party in Cyber Notary Concept in Indonesia - Ganandhika, Anak Agung Bagus Ryan; Pratama, Putu Rama Ari; Putra, Made Panji Ambara; Utama, I Wayan Kartika Jaya (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
The purpose of this study is to determine the application of trusted third parties in the concept of cyber notary in Indonesia with two problems, namely the application of the concept of cyber notary and the application of trusted third parties in the concept of cyber notary increases the ease index by notaries in carrying out their duties. This study applies a method called the normative method because the legislation has regulated the concept of cyber notary. The results of this study refer to the concept of cyber notary interpreted solely as a digital transaction certificate, does not have strong legal force in Indonesia, but this cyber notary can be applied through UUJN which is regulated more deeply by being regulated in legislation.